Cartografia de afetos e cibercartografia em fluxos - Renata do Carmo Crisostomo Nakano (2015)
This masters degrees dissertation was completed in the Art Postgraduate Program, within the line of research of Poetic Tecnology at Minas Gerais University. From the perspective of cartography in flow the research connects the concepts of affect in Espinosa agency in Deleuze and perception Merleau-Ponty in order to analyze the cybercartografy from the interactive perspective.Comparative analysis between cybercartografy and the concept of affect in interactive art in which the cibercartografia nothing but a Cartesian perspective to a process of co-creation between technology and users from which to create living body maps in action.The cybercartography turns from the perspective of the agency as episode and eventwhich refers both Situationists drift as the analysis of relational space from Massey. With case studies of projects Transmedia City and Sensory Maps the interaction process made possible by the technology becomes understood then the poetic perspective from actions that take place between the entities in which the movements caused by the desires keeps the possibility of transforming cibercartografia on experience with art.